As muralhas romanas do Porto: um balanço arqueológico - Silva, António Manuel (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The article discusses Roman walls of ancient Oporto town, settled on Cathedral hill from Late Bronze Age, according to archaeological data produced during latest decades, mainly as a result of the continuous rescue and field evaluation policy Town Hall has developed through its former Urban Archaeology Unit. Due to this work, near a dozen of a defensive wall sections were already recognized, dating from the end of Iron Age, till 1st/2nd and 3rd/4th centuries, which suggests several building or rebuilding phases on the same wall.